The Effect of Ease of Use and Customer Trust toward Customer Satisfaction and Customer Loyalty in Using the Shopee PayLater Feature in Pekanbaru City - Tengku Firli Musfar; Nabilla, Mutiya; Jushermi Jushermi (Dinasti Publisher, 2023)
The study aims to analyze the effect of ease of use and consumer trust toward consumer satisfaction and consumer loyalty in using the Shopee PayLater feature. This study is a quantitative research and primary data was collected by questionnaire. The population in this study is the people of Pekanbaru city who have used Shopee PayLater. The sampling technique used is non-probability sampling with purposive sampling. The subjects of this study were 112 respondents. For data analyze using path analysis with SPSS 25. The result shown that ease of use and customer trust have positive and significant effect to customer satisfaction and customer loyalty in using the Shopee PayLater Feature, ease of use and customer trust has positive and significantly effect to customer loyalty through customer satisfaction, and customer satisfaction has positive and significantly effect to customer loyalty in using the Shopee PayLater Feature in Pekanbaru city.